ArmA and RmtB Were the Predominant 16S RMTase Genes Responsible for Aminoglycoside-resistant Isolates in Korea - Lee, Tae Hee (J Korean Med Sci, 2018)
Pathogenic gram-negatives that produce 16S ribosomal RNA methyltransferases (16S RMTases) have already been distributed all over the world. To investigate the predominance of aminoglycoside resistance associated with 16S RMTases in Korea, we collected a total of 222 amikacin resistant Gram-negative clinical isolates from patient specimens between 1999 and 2015 from three hospital banks across Korea. ArmA and rmtB were the predominant 16S RMTase genes responsible for aminoglycoside-resistant isolates circulating in Korean community settings although only one rmtA-producing isolate was detected in 2006.